EVALUASI PROGRAM MA’HAD ALJAMIAH IAIN SULTHAN THAHA SAIFUDDIN JAMBI (PENERAPAN MODEL CIPP DAN DEM) - Zawaqi Afdal Jamil (Jurnal Evaluasi Pendidikan, 2020)
The objective of this study is to investigate the implementation effectivity of Ma’had alJamiah Program in IAIN Sulthan Thaha Saifuddin Jambi. The design of the study is evaluative survey by applying CIPP and DEM evaluation models. In this research, the evaluation result level is devided into five categories, that are: very good, good, moderate, fair, and not applicative program. The result of the study is Ma’had alJamiah Program included in moderate category. Some reasons for stating the program included in this category are the college does not have any permanent clasrooms, students’ desks and chairs, library, book references, and mosque. Ma’had alJamiah does not have specific curriculum in learning process program. Most of the lecturers do not make learning plan. They do not evaluate students’ learning performance, both theory and application in the way of doing practice worship. Based on the results of the study it is recommended to the leaders of Al-Jami'ah Ma'had to fulfil infrastructure the college and remind the lecturers to prepare lesson plans and carry out the evaluation of both theory and application in the way of doing practice worship learning. Keywords program evaluation, Ma’had alJamiah, cipp and dem models